Role of sociocultural context in teachers' information and communication technology integration in selected public primary schools in Malaysia - Mohamad @Razak, Nor Asiah (2019)
A tremendous capital expense for Information and Communication Technology (ICT) integration programmes including to train teachers does not guarantee that teachers integrate ICT in teaching in schools. According to a reports by the Malaysia’s Ministry of Education (MOE), approximately 80% of teachers spent less than one hour a week integrating ICT in teaching. Similarly, United Nations Educational, Scientific and Cultural Organisation (UNESCO) reports revealed that teachers’ ICT integration in Malaysian schools has not gone much further than the use of word-processing application as an instructional tool in teaching. Recent studies in Malaysia indicate that there was a minimal ICT integration in schools. Therefore, there is a need to understand why teachers’ ICT integration in teaching in Malaysia is minimal despite pockets of promising practices on ICT integration programmes. This study explores the role of sociocultural context on teachers’ ICT integration in Malaysian public primary schools on the success of ICT integration. To understand the different sociocultural contexts, this study employs the Cultural-Historical Activity Theory (CHAT) to explore the ‘mediators’ of different sociocultural contexts that influence teachers’ ICT integration in teaching. This study also sought to explain how the ‘contradictions’ and the causes of the ‘contradictions’ in different sociocultural contexts that hinder teachers’ ICT integration in teaching. Lastly, this study explains how ‘contradictions’ within the different sociocultural contexts that influence teachers’ ICT integration in teaching are resolved. This study utilised a qualitative methodology with a multiple-case study approach. A research paradigm employed was social constructivism. CHAT was employed as an analytic lens which incorporates Activity Systems Analysis (ASA) to analyse three intertwined contexts (classroom, department, school) of ICT integration activities related to teachers in three activity settings. Three levels of in-depth-interviews were used for primary data collection to acquire the participants’ experiences in the school’s social environments. A within-case analysis, utilising qualitative content analysis incorporates the ‘inductive category formation technique’ to navigate each case study data in order to construct the categories. For constructing the themes, a cross-case analysis utilised the constant comparative technique to observe similarities and differences, and typicality and diversity between both cases. This study also discussed the trustworthiness of the data to ensure the rigor and robustness of the study is ensured. One of the strategies for trustworthiness that used in this study was triangulation. One of the triangulation techniques to validate the primary data collection that used in this study were non-participant observations, field notes, and document analysis. The findings of the study revealed three ‘mediators’ within different activity systems in a school’s sociocultural context that influenced teachers’ ICT integration in teaching: 1) types of tools in the school, 2) rules and regulations in the school that shape the ICT culture, and 3) division of labour in a collective context of the school community. The findings also uncovered three themes for existing ‘tensions’ and resolving ‘tensions’. Three themes for ‘contradictions’ and causes of ‘contradictions’ categories involve the inadequate schools’ ICT facilities due to financial constraints, failure to commit to the schools’ regulations due to time constraints, and failure to comply with the schools’ regulations due to resistance to change. The three themes for the resolutions of ‘contradictions’ category is assisted performance, sharing ideas, and distributed leadership style. In conclusion, school stakeholders should work hand-in-hand to resolve uprising tensions and reckon their respective roles in working to ensure the success amidst teachers to integrate ICT in teaching. The most influential role reflects the leadership styles that place focus on distributed leadership, which serves as a catalyst in influencing the teachers to integrate ICT. This study points to several relevant implications for policymakers, school administrators, and teachers in shared ownership to address the ‘contradictions’, as well as the causes of ‘contradictions’, in varied sociocultural contexts that affect teachers to integrate ICT towards successful ICT integration across schools. Integrating ICT in teaching is not without its own set of drawbacks, wherever and whenever issues arise, efforts from the school community, including alumni and local business owners, which offer strong social and financial support. Leadership quality in distributed leadership style adopted by both headmasters and ICT coordinators in transferring their duties to their subordinates to manage ICT integration activities has also led the teachers to succeed in integrating ICT across schools. Despite the scarcity of this particular subject matter, this study has put forward crucially sought lessons for successful implementation of ICT integration, from which other schools that share similar characteristics and contexts may benefit.